Availability and Use of Technology Among SME Entrepreneurs in Mumbai and Navi Mumbai - Acharya, Namrata; Shinde, Govind (AMC Indian Journal of Entrepreneurship, 2022)
The present research paper discussed the role of information and communication technology (ICT) within the small and medium enterprise (SME) sector in Mumbai and Navi Mumbai. ICT plays a significant role in maintaining business operations and to make businesses globally competitive. SMEs play a very important role in the economic growth and development in an economy and thus, it is important to focus on making them globally competitive with the use of ICT , as use of outdated technology or lack of technology also hampers growth of SMEs in India. The research focused on studying the availability and use of technology by entrepreneurs of SMEs in Mumbai and Navi Mumbai. The use of outdated technology or low level of use is one of the problems faced by SMEs to beat growing competition. SMEs should make use of different ICT tools for increasing competitiveness of their business. This research paper focused on availability and use of technology using structured questionnaire for data collection.